设A,B为两个事件,则概率P(A+B)=
A: P(A)+P(B)
B: P(A)+P(B)-P(A)P(B)
C: 1-P([img=14x22]18038f8f8e8728a.png[/img] [img=14x22]18038f8f9721ea1.png[/img])
D: 1-P(A)P(B)
A: P(A)+P(B)
B: P(A)+P(B)-P(A)P(B)
C: 1-P([img=14x22]18038f8f8e8728a.png[/img] [img=14x22]18038f8f9721ea1.png[/img])
D: 1-P(A)P(B)
举一反三
- 设A、B是两事件,且B[img=14x17]1803b0b1247edd6.png[/img]A,则 A: P([img=34x22]1803b0b12cb8ceb.png[/img])=1-P(A) B: P(B-A)=P(B)-P(A) C: P(B|A)=P(B) D: P(A|[img=14x22]1803b0b1351541a.png[/img])=P(A)
- 设[img=143x35]1803b3baa24b1c3.png[/img],其密度函数为f(x),分布函数为F(x),则 A: P(X<0)=P(X>0) B: P(X<1)=P(X>1) C: F(−x)=1−F(x) D: f(−x)=f(x)
- 设随机变量[img=93x25]180327943b4d5c6.png[/img],分布函数为F(x),密度函数为f(x),则有( ) A: P(X<0)=P(X>0) B: f(x)=f(-x) C: P(X<1)=P(X>1) D: F(x)=F(-x)
- 设随机变量[img=93x25]1803da321872708.png[/img],分布函数为F(x),密度函数为f(x),则有( ) A: P(X<0)=P(X>0) B: f(x)=f(-x) C: P(X<1)=P(X>1) D: F(x)=F(-x)
- 设事件E、F互斥,概率P(E)=p,P(F)=q,则P()是() A: q B: 1-q C: p D: 1-p